2010
DOI: 10.1038/ismej.2010.135
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide induces phosphate release from polyphosphate in cultures of a marine Beggiatoa strain

Abstract: Sulfur bacteria such as Beggiatoa or Thiomargarita have a particularly high capacity for storage because of their large size. In addition to sulfur and nitrate, these bacteria also store phosphorus in the form of polyphosphate. Thiomargarita namibiensis has been shown to release phosphate from internally stored polyphosphate in pulses creating steep peaks of phosphate in the sediment and thereby inducing the precipitation of phosphorus-rich minerals. Large sulfur bacteria populate sediments at the sites of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 37 publications
4
156
0
1
Order By: Relevance
“…This has been interpreted as release of P under anoxic conditions when these organisms degrade their intracellular polyphosphate storage that was built up under oxic conditions, to gain energy. Recently, transient uptake and release of P under oscillating redox conditions has been reported for the giant sulfide-oxidizing bacteria Thiomargarita namibiensis and members of the genus Beggiatoa (Schulz and Schulz 2005;Goldhammer et al 2010;Brock and Schulz-Vogt 2011). Widespread occurrence of filamentous sulfur bacteria on the Peruvian shelf and upper slope was observed in sediment samples and in seafloor images acquired during the same cruise (T. Mosch unpubl.).…”
Section: Discussionmentioning
confidence: 97%
“…This has been interpreted as release of P under anoxic conditions when these organisms degrade their intracellular polyphosphate storage that was built up under oxic conditions, to gain energy. Recently, transient uptake and release of P under oscillating redox conditions has been reported for the giant sulfide-oxidizing bacteria Thiomargarita namibiensis and members of the genus Beggiatoa (Schulz and Schulz 2005;Goldhammer et al 2010;Brock and Schulz-Vogt 2011). Widespread occurrence of filamentous sulfur bacteria on the Peruvian shelf and upper slope was observed in sediment samples and in seafloor images acquired during the same cruise (T. Mosch unpubl.).…”
Section: Discussionmentioning
confidence: 97%
“…These bacteria release phosphate from internally stored polyphosphates upon exposure to anoxia and sulphide, as demonstrated in laboratory experiments for Beggiatoa (Brock and Schulz-Vogt 2011). The bacterial release of phosphate from polyphosphates in Thiomargarita namibiensis has been shown to lead to the episodic formation of phosphorus-rich minerals in sediments off the coast of Namibia (Schulz and Schulz 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Sulphur-oxidising bacteria are also thought to play a critical role in the formation of authigenic Ca-P minerals by releasing PO 4 from polyphosphates in their cells (Brock and Schulz-Vogt 2011;Schulz and Schulz 2005) and driving pore waters to supersaturation with respect to authigenic Ca-P minerals. Our results show, however, that there is no clear difference between authigenic Ca-P concentrations in suspended matter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They can accumulate large amounts of nitrate and elemental sulfur, and use them for respiration. In addition to the elements mentioned above, nitrate-storing sulfur oxidizers may influence the phosphorus cycle, as it has been shown that some of them accumulate phosphorus as polyphosphate in their cells [4,39]. The intracellular accumulation of polyphosphate to overcome physical and chemical stress is widespread among microorganisms [5,12,23,28], although absence of polyphosphate granules in cells of Thioploca has been repeatedly reported [14,15,16,22].…”
Section: Introductionmentioning
confidence: 99%